Can 'learning spaces' shape transboundary management processes? Evaluating emergent social learning processes in the Zambezi basin. Issue 97 (July 2019) - Lumosi, Caroline K.; Pahl-Wostl, Claudia; Scholz, Geeske
Highlights: We evaluated long-term emergent social learning processes within transboundary river basin management in the Zambezi basin. We found the concept of learning space helpful to evaluate long-term emergent social learning processes and outcomes. Emergent processes in the Zambezi basin were key in the development of formal structures for basin-wide management. Emergent processes are relevant for expediting formal processes by stimulating physical and structural learning spaces. Abstract: Social learning in collaborative processes is considered important for addressing complex natural resource dilemmas and for supporting multi-actor interactions in joint problem framing, and the co-construction of solutions. While social learning is often presented as a normative approach for stimulating shared understanding among multiple actors, little is known about how long-term emergent social learning processes occur. In this paper, we analyse a long-term emergent social learning process within transboundary river basin management. To this end, we apply the concept of the learning space - meaning arenas for interaction, deliberation and re-framing - as a lens for evaluating emergent social learning processes. Results show that in the Zambezi Basin, social learning in emergent processes occurs in stages and is triggered by various factors that result in collective outcomes throughout the process. Emergent social learning processes were triggered by structural reorganization processes, natural calamities, the influences of cooperating partners and international frameworks. Over time, the spaces for interaction and deliberation led to the reframing of basin management practices and the subsequent development of new institutions. In addition, social learning outcomes included increased relational capacities of national and regional actors and trust, but also mistrust and power issues. While emergent long-term processes are difficult to evaluate, our findings reveal that the concept of the learning space provides a structure for assessing long-term emergent social learning process outcomes, and thus, can provide a broader understanding of processes needed in designing long-term management practices or institutions.